Methane Concentration in Mud Conduits of Submarine Mud Volcanoes: A Coupled Geochemical and Geophysical Approach. (5th February 2019) - Kioka, A.; Tsuji, T.; Otsuka, H.; Ashi, J.
Abstract: Mud volcanoes are among the largest geological sources releasing methane gas. Numerous studies have revealed their origins and compositions released from submarine mud volcanoes. However, quantification of the amount of gas inside submarine mud volcanoes has been challenging due to the difficulty of in situ measurements, which has hampered better evaluation for their contribution to the global methane budget. Here we provide a coupled geochemical and geophysical model that bridges bulk methane concentrations and seismic wave velocities in the mud conduit of submarine mud volcano. This model is applicable to most submarine mud volcanoes and is able to estimate methane concentration at the upper several hundreds of meters in the mud conduits using downhole logging data or seismic data. Our calculation for submarine mud volcanoes in the Eastern Mediterranean and the Nankai plate subduction zones shows that the weight fractions of gaseous and dissolved methane in total weight of sediment are 1, 000–3, 500 ppm within their mud conduits, which are much higher than previously expected from pore‐water evidence from conventional shallow subsurface sampling. Although more definitive calculations cannot be made until the model parameters are better constrained, our approach provides an opportunity for re‐estimating the global methane budget in submarine mud volcanoes, shedding new light upon the impact of submarine mud volcanism on carbon cycle. Key Points: Gaseous and dissolved methane in the conduits of submarine mud volcanoes is studied by a new coupled geochemical and geophysical approach Studied submarine mud volcanoes showed higher methane concentrations than expected from conventional measurements of sediment cores Our new approach helps reassess a global methane budget in offshore mud volcanoes and their role on global carbon cycle